2013
DOI: 10.1126/scisignal.2003374
|View full text |Cite
|
Sign up to set email alerts
|

An Adenosine-Mediated Signaling Pathway Suppresses Prenylation of the GTPase Rap1B and Promotes Cell Scattering

Abstract: During metastasis, cancer cells acquire the ability to dissociate from each other and migrate, which is recapitulated in vitro as cell scattering. The small guanosine triphosphatase (GTPase) Rap1 opposes cell scattering by promoting cell-cell adhesion, a function that requires its prenylation, or posttranslational modification with a C-terminal isoprenoid moiety, to enable its localization at cell membranes. Thus, signaling cascades that regulate the prenylation of Rap1 offer a mechanism to control the membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
136
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(141 citation statements)
references
References 52 publications
5
136
0
Order By: Relevance
“…(31) and invasiveness in breast carcinoma (40). In fact, A2BR has been suggested to negatively regulate cell adhesion by modulating the localization of Rap1 protein (41). Others have suggested that A2BR controls carcinoma proliferation via HIF1a activation, indicating that A2BR may have several mechanisms to regulate tumor progression (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…(31) and invasiveness in breast carcinoma (40). In fact, A2BR has been suggested to negatively regulate cell adhesion by modulating the localization of Rap1 protein (41). Others have suggested that A2BR controls carcinoma proliferation via HIF1a activation, indicating that A2BR may have several mechanisms to regulate tumor progression (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Most interestingly, the A 2B adenosine receptor has recently been identifi ed as a target of the metastasis-inducing transcription factor FOS -related antigen 1 (FRA1) in TNBC ( 27 ). Ntantie and colleagues ( 28 ) further unraveled a signaling pathway linking A 2B adenosine receptor signaling and tumor cell adhesion. Taken together, these studies converge to suggest an important role for the CD73-A 2B axis in metastatic dissemination, independently of immunosuppression.…”
Section: Mini Reviewmentioning
confidence: 99%
“…21 Williams has extended this finding to hypothesize that prenylation of RhoA might be similarly negatively regulated by phosphorylation of Ser188. 22 It follows that reduction of Myc-RhoC-R188S membrane association might also be due to acquisition of phospho-Ser188 regulation of prenylation that obstructs processing events needed for effective membrane intercalation of the GTPase.…”
Section: Discussionmentioning
confidence: 97%